2014
DOI: 10.4102/jsava.v85i1.1110
|View full text |Cite
|
Sign up to set email alerts
|

Serological detection of infection with canine distemper virus, canine parvovirus and canine adenovirus in communal dogs from Zimbabwe

Abstract: Domestic dogs are common amongst communities in sub-Saharan Africa and may serve as important reservoirs for infectious agents that may cause diseases in wildlife. Two agents of concern are canine parvovirus (CPV) and canine distemper virus (CDV), which may infect and cause disease in large carnivore species such as African wild dogs and African lions, respectively. The impact of domestic dogs and their diseases on wildlife conservation is increasing in Zimbabwe, necessitating thorough assessment and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
3
14
0
Order By: Relevance
“…It is worth knowing that the low incidence rate of 13.4% reported here is purely based on clinical cases from hospitalization. The incidence in the general dog population may be greatly higher as found in earlier reports in Africa including Nigeria [10] [14] [21]. Furthermore, reasons for breed susceptibility still remain unclear; however, CPE was more significantly associated with Alsatian (49.0%), Mongrels (25.0%), Rottweiler (7.8%) and local dog (indigenous) breeds (5.9%) as compared with the other seven breeds in this study.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…It is worth knowing that the low incidence rate of 13.4% reported here is purely based on clinical cases from hospitalization. The incidence in the general dog population may be greatly higher as found in earlier reports in Africa including Nigeria [10] [14] [21]. Furthermore, reasons for breed susceptibility still remain unclear; however, CPE was more significantly associated with Alsatian (49.0%), Mongrels (25.0%), Rottweiler (7.8%) and local dog (indigenous) breeds (5.9%) as compared with the other seven breeds in this study.…”
Section: Discussionsupporting
confidence: 45%
“…Nonetheless, some reports available to us indicate that the disease is relatively high in dogs screened across the continent. In Nigeria and South Africa for instance, 30/31 (96.77%) and 106/108 (98.15%) dogs, respectively tested positive to parvovirus [10] while in Zimbabwe serological survey indicated 191/225 (84.89%) of dogs screened had antibodies to CPV [21]. Most of the studies in Africa cited in this work focused less on the possible risks factors of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…3). However, these numbers may change as there are several other countries where current studies are based on CPV positive serology testing, namely Cape Verde (Castanheira et al, 2014), Pakistan (Muzaffar et al, 2006) or Zimbabwe (McRee et al, 2014).…”
Section: The Worldwide Distribution Of Antigenic Cpv-2 Variants Spreamentioning
confidence: 99%
“…Previously, Cha et al (2012) showed that the seroprevalence of CPV in wild raccoon dogs (Nyctereutes procyonoides) from South Korea was 44.1%; McRee et al (2014) reported that 34% and 84% samples were detected to be positive to CDV and CPV, respectively in communal dogs from Zimbabwe; the CDV and CPV seroprevalences were 61% and 47%, and 89% and 72% in urban and rural areas, respectively in the Araucanía region in Chile (Acosta-Jamett et al, 2015). In the current research herein, the overall prevalence of CDV, CPV, and both viruses a Differences among the ages were found statistically significant of CDV infection in pet dogs (P<0.01,  2 =646.425).…”
Section: Indian Journal Of Animal Researchmentioning
confidence: 99%